2019
DOI: 10.1080/16549716.2019.1646036
|View full text |Cite
|
Sign up to set email alerts
|

Measuring maternal near-miss in a middle-income country: assessing the use of WHO and sub-Saharan Africa maternal near-miss criteria in Namibia

Abstract: Background : Namibia, a middle-income country in sub-Saharan Africa (SSA), plans to use the Maternal Near Miss (MNM) approach. Adaptations of the World Health Organization (WHO) MNM defining criteria (‘WHO MNM criteria’) were previously proposed for low-income settings in sub-Saharan Africa (‘SSA MNM criteria’), but whether these adaptations are required in middle-income settings is unknown. Objective : To establish MNM criteria suitable for use in Namibia, a middle-income co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
(41 reference statements)
5
20
2
Order By: Relevance
“…Laparotomy for ectopic pregnancy was only included if blood loss was ≥1000 mL, blood was transfused or if patient was hemodynamically unstable [ 12 ];…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laparotomy for ectopic pregnancy was only included if blood loss was ≥1000 mL, blood was transfused or if patient was hemodynamically unstable [ 12 ];…”
Section: Methodsmentioning
confidence: 99%
“…Following this concept, organ dysfunction markers (25 criteria) define MNM [ 2 ]. However, several studies in different settings demonstrated that the organ-dysfunction criteria may not be suitable and proposed adapted criteria to prevent underreporting of life-threatening disorders [ 8 - 12 ]. In 2017, a Delphi study suggested adaptations to the WHO-criteria for low-resource settings in Sub-Sahara Africa (SSA) [ 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other terms reported in more recent studies, such as cesarean section, preeclampsia, severe maternal outcome (smo), termination, case fatality rate, association and potentially life-threatening condition (pltc), as wellas terms that describe countries such as Brazil, Ethiopia, India, and Tanzania reflect that, in recent years, the authors have been conducting studies that measure the cases and rates of MNM according to specific maternal health conditions and their associated factors, [21][22][23][24][25] or studies for the validation of the MNM criteria in these countries. [26][27][28][29] Terms related to severe acute maternal morbidity were not included, since this is a term interchangeable with MNM, and the WHO does not recommend refering to severe, life-threatening obstetric complications. Similarly, since we did not include articles that did not have MNM as the main subject mentioned in the title, abstract or keywords, it is possible that some studies that evaluated MNM but did not include this information in these fields may have been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The maternal mortality also is high as 265/100 000 live birth in 2015 [18]. The common causes of maternal and child mortality include postpartum hemorrhage, eclampsia, preterm birth and low birth weight [19]. All these conditions have been linked with sub-optimal IPI in the previous studies.…”
Section: Introductionmentioning
confidence: 99%